Analisis Kendala Guru PAUD dalam Menyusun Rencana Pelaksanaan Pembelajaran Harian (RPPH): Studi Literatur - Fakhira Azzahra Syarefi; Gustiana G; Luthfiah Amri Rambe; Yulenta Carolin Sitiani Duha; Elya Siska Anngraini (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Learning planning is an important component in the implementation of early childhood education (ECE). One form of learning planning used by ECE teachers is the Daily Learning Implementation Plan (RPPH). However, in practice many teachers still experience difficulties in preparing RPPH systematically and in accordance with the applicable curriculum. This study aims to identify the challenges faced by early childhood teachers in preparing RPPH and to find solutions or strategies that can improve the quality of its preparation. This study uses a literature review (library research) method by examining various sources such as books, scientific journals, and research articles relevant to the research topic. The article search was conducted through Google Scholar using keywords related to RPPH in early childhood education. From the screening results, six relevant articles were selected for further analysis. The results show that there are still several problems in preparing RPPH, such as low teacher competence in designing learning plans, lack of understanding of RPPH components, and the suboptimal implementation of innovative learning approaches such as STEAM. In addition, curriculum changes require teachers and prospective teachers to have better abilities in preparing RPPH. Therefore, continuous training, workshops, and academic supervision are needed to improve teachers’ competence in developing quality learning plans.